Numerical investigation and modelling of solar photovoltaic/thermal systems / Afroza Nahar - Afroza, Nahar (2017)
Solar energy is the most promising resource among all other renewable energy, because of its inexhaustible supply, environmental friendly notion and options for harnessing the energy directly from the Sun. Solar energy may be harvested as thermal energy by solar thermal collector (STC) as well as electrical energy through solar photovoltaic (PV) module. Hybrid photovoltaic thermal (PV/T) module is combination both of these solar thermal and PV which is a well-engineered solar co-generation system in one physical profile. One of the major shortcomings of PV technology is its poor energy conversion efficiency; commercially available solar cells have efficiency from 4 to 17%. Moreover, traditional silicon solar cells suffer from a drop in efficiency by 0.4–0.65% per degree increase in cell temperature. The heat produced in the PV cells which would otherwise be wasted, is taken away to make use in different thermal applications. The main problem of PV/T is the effectual removal of heat from the module and transfers heat to end users for making efficient utilization. In the present research, attempt has been made to design and develop several configurations of thermal collector with the novel concept of excluding absorber plate. This elimination of absorber plate from thermal collector is done with a view to make the design simple and ensuring well integration with PV module. In addition, elevation head has been employed to maintain the circulation of water inside the flow channel in order to save the power that would otherwise be consumed in pumping. A three-dimensional mathematical model of PV/T module based on the above concept is developed and simulated in finite element based (FEM) based software COMSOL Multiphysics®. The validation of the model has been ascertained through outdoor experimentation for a representative design. In numerical simulation, effect of various parameters like inlet velocity, water inlet temperature and environment conditions like irradiation, ambient temperature have been investigated to evaluate the performance of PV/T module. All of the investigations are made with two channel materials: aluminum and copper. The numerical results with the representative design were found to be in well agreement with the corresponding experimental outcomes. Based on this validated mathematical model, performance of the other designs has been evaluated by numerical simulation. Also, numerical results show that thermal performance without absorber plate was found as good as that with absorber plate. Maximum overall efficiency of the PV/T has been obtained with parallel plate flow configuration. For aluminum and copper flow channels, the overall efficiencies are 86% and 89%, respectively. The highest output power of 129.2 W and the maximum electrical efficiency of 12.6% are achieved with copper channel of same flow design. Regarding the effect of channel materials on PV/T performance, no significant dominance of any of the material aluminum or copper was found. In the present research, a new concept of thermal collector without absorber plate has been proposed and the performance of PV/T is found acceptable using this collector. This type of thermal collector reduces the weight and cost of the system.